Análise através do método dos elementos finitos das tensões desenvolvidas no reborbo alveolar sob as próteses totais com três diferentes conceitos oclusais - Ferreira, Luciano Pedrin Carvalho [UNESP] (2011)
The strain distribution patterns in the alveolar residual ridge as a consequence of occlusal loads applied in complete dentures constructed with different occlusal schemes are not known. The aim of this study was to develop a comparative and qualitative analysis of the strains generated in the right first molar region of the supporting structures of a mandibular complete denture using the two-dimentional Finite Element Analysis (FEA-2D). Coronal section two-dimensional models were developed reflecting mandibular complete dentures constructed with three different schemes of occlusion, namely conventional (CO), Lingualized (LO) and monoplane (PO). The models also had variations in the contour of the supporting structures, representing four conditions of residual ridge resorption: (1) high, well rounded; (2) knife edge; (3) low, well rounded, and (4) depressed. Two materials of artificial teeth were considered: acrylic resin and porcelain. A vertical load of 50 N was applied onto the occlusal surface of the mandibular right first molar. The software GID (International Center for Numerical Methods in Engineering, Barcelona, Spain) generated images of Von Mises (stress) and vertical (compression or tensile) strains in the FEA-2D models. Within the limitations of this study the following conclusions were drawn: (1) Stress and compression were observed in the supporting structures with all of the studied occlusal schemes; (2) The distribution of stress and compression with CO dentures generated patterns of intensity with the appearance of horizontal layers and, with LO and PO dentures with the appearance of vertical layers; (3) With CO dentures the intensity of stress and compression increased progressively from the crest of the residual ridge to the alveolar bone and, with LO and PO dentures from the buccal to the lingual slope of the ridge; (4) With all of the studied occlusal schemes, neither the...